A study of serum electrolytes in severe acute malnourished children with and without complications - Dakshayani, B; Ravi, Monisha; R, Premalatha (Indian Journal of Child Health, 2018)
Objective: Children with severe acute malnutrition (SAM) are categorized into “complicated and uncomplicated cases” based on clinical criteria alone. Electrolyte imbalance is one of the prognostic factors in severe malnutrition. We aimed to study serum electrolytes in complicated and uncomplicated SAM children. Methods: This was a cross-sectional observational study conducted at the nutritional rehabilitation center of a tertiary care hospital attached to a medical college from May 2016 to April 2017. Children between the ages of 1 month and 5 years who met the World Health Organization criteria for SAM were included in the study. Serum electrolytes were estimated with an automated analyzer by ion selective electrode method. Results: Among 113 SAM children included, 71 had complications and 42 were without complications. The mean value of serum sodium was 134.58±5.45 meq/L, potassium was 4.29±0.75 meq/L, and chloride was 103.31±7.16 meq/L. Hyponatremia was seen in 43.4% and hypokalemia in 7.1% of children. There was no statistically significant difference in the mean values of serum electrolytes and frequency of hyponatremia and hypokalemia between groups. Conclusion: Dyselectrolytemia occurs in SAM children with and without complications. Serum electrolyte levels may need to be measured in all SAM cases to detect asymptomatic hyponatremia and hypokalemia. This will help in triaging those with asymptomatic hyponatremia and hypokalemia to inpatient care.